MEMPERTAHANKAN PRINSIP-PRINSIP PENGEMBANGAN POTENSI SPIRITUAL YANG TRANSENDENTAL - Akmansyah, M. (Universitas Islam Negeri Raden Intan Lampung, 2015)
The phenomenon of the rise of the spiritual and thedecline of traditional religion become a global trend,not only in Indonesia, but also in many othercountries. While there may be an increase in thenumber of avowed atheists and agnostics, there is alsoas “spiritual but not religious.” Spiritualism becamethe answer to the mental and psychological excesses ofmodern people especially those living in urban areas.In addition, a number of sects and schools of thoughtwhich later became the foundation of many spiritualeducations began to emerge, or at least have a lot ofnew findings and approaches as a result of the findingsof modern science, to develop spiritual dimension.This article will discuss further abaut thatphenomenon.